2021
DOI: 10.3389/fneur.2021.678794
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vascular Risk Factors on Post-stroke Cognitive Impairment: The Nor-COAST Study

Abstract: Introduction: Post-stroke cognitive impairment (PSCI) is common, but evidence on the impact of vascular risk factors is lacking. We explored the association between pre-stroke vascular risk factors and PSCI and studied the course of PSCI.Materials and Methods: Vascular risk factors were collected at baseline in stroke survivors (n = 635). Cognitive assessments of attention, executive function, memory, language, and the Montreal Cognitive Assessment (MoCA) were performed at 3 and/or 18 months post-stroke. Strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…One interesting study demonstrated that language improvement was noted particularly in patients with diabetes mellitus, as well as in patients with hypercholesterolemia and coronary artery disease. 32 For late PSCI, patients with stroke and type 2 diabetes mellitus have worse cognitive function after 2 years. 17 , 33 , 34 During the chronic phase, diabetes mellitus may even outweigh the effects of severe mesial temporal atrophy.…”
Section: Diabetes Mellitus and Psci /Post‐stroke D...mentioning
confidence: 99%
“…One interesting study demonstrated that language improvement was noted particularly in patients with diabetes mellitus, as well as in patients with hypercholesterolemia and coronary artery disease. 32 For late PSCI, patients with stroke and type 2 diabetes mellitus have worse cognitive function after 2 years. 17 , 33 , 34 During the chronic phase, diabetes mellitus may even outweigh the effects of severe mesial temporal atrophy.…”
Section: Diabetes Mellitus and Psci /Post‐stroke D...mentioning
confidence: 99%
“…Complementary information regarding definitions; the cognitive test battery 2 , 19 , 29 ; plasma samples; and statistics are described in the Supplemental Material .…”
Section: Methodsmentioning
confidence: 99%
“…All participants in LAST-long undergo evidence-based comprehensive stroke unit treatment in the acute phase and further rehabilitation according to individual needs after discharge from hospital. 12 The rehabilitation usually consists of inpatient rehabilitation, rehabilitation in the patient’s home or at an outpatient clinic and is often limited to the first 3 months for patients with mild-to-moderate strokes but can last for up to 6 months for patients with the most severe strokes and for selected patients even longer. According to the National guidelines, patients are offered a follow-up consultation at the stroke units’ outpatient clinic 3 months after stroke.…”
Section: Methodsmentioning
confidence: 99%